2009
DOI: 10.1161/strokeaha.109.555540
|View full text |Cite
|
Sign up to set email alerts
|

Walking After Stroke: What Does Treadmill Training With Body Weight Support Add to Overground Gait Training in Patients Early After Stroke?

Abstract: on behalf of Gruppo Italiano Studio Allevio Carico Ictus (GISACI)Background and Purpose-This study aimed to assess the effectiveness of gait training using body weight support on a treadmill compared with conventional gait training for people with subacute stroke who were unable to walk. Methods-This was a single-blind, randomized, controlled trial with a 6-month follow-up. Ninety-seven subjects were recruited within 6 weeks of stroke onset and were randomly assigned to conventional rehabilitative treatment pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 18 publications
7
116
0
4
Order By: Relevance
“…For BWS treadmill training, exercise tolerance was set based on several reports 9,10,13,14,[18][19][20] . Because walking backwards is a difficult task, we started with a low load, increasing the speed and time as the experiment progressed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For BWS treadmill training, exercise tolerance was set based on several reports 9,10,13,14,[18][19][20] . Because walking backwards is a difficult task, we started with a low load, increasing the speed and time as the experiment progressed.…”
Section: Methodsmentioning
confidence: 99%
“…However, because walking backwards involves a high risk of falls, only stroke patients in the chronic phase with a quasi-stable gait should undergo this type of training. For walking forwards, partial body weight support (BWS) training has been performed as a therapeutic intervention using a treadmill for patients lacking a fully stable gait in the early stage o f r e h a b i l i t a t i o n , a n d i s p u r p o r t e d l y effectiveness 9,10) ; provided that there are reports to the effect that a training has an effect and those to the effect that any effect can hardly be expected in a systematic review 11,12) . One report showed no significant difference between this training and conventional training, particularly in acute-phase s t r o k e r e h a b i l i t a t i o n 1 3 , 1 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Gait endurance is the ability to sustain muscle activities related to balance, lower extremity coordination, muscle strength and muscle function weakness, and energy consumption 25) . Son 26) analyzed respiration gas, and observed that more energy was consumed during treadmill gait.…”
Section: Discussionmentioning
confidence: 99%
“…Task oriented functional training on weight-bearing was especially effective 11,12) . In Frenceshini and colleagues' study 13) , stroke patients' trunk control ability improved after treadmill gait training, which to improved balance ability. When stroke patients performed standing in functional strengthening training, the rate of weight bearing on the affected side increased, improving their balance ability 11) .…”
Section: Introductionmentioning
confidence: 92%